연속된 무릎 손상 후 발생한 슬개골 근위부 소매 골절 - 정홍준(Hong Jun Jung); 현충수(Chung-Su Hyun); 남태석(Tae-Seok Nam) (The journal of the Korean Orthopaedic Association, 2023)
슬개골 소매 골절은 미성숙 골격을 가진 소아기나 청소년기에 간혹 관찰된다. 또한, 대부분의 슬개골 소매 골절은 원위부에서 흔히 관찰되며, 드물게 근위부에서 관찰된다. 저자들은 15세 남아에서 발생한 슬개골 근위부 소매 골절에 대해 보존적 치료를 통해만족할만한 결과를 보였음을 보고하고자 한다. 또한, 문헌 고찰을 통해 다수의 증례가 비슷한 병력을 가지고 있어 이에 대해 분석해 보고자 한다 Sleeve fractures of the superior pole of the patella are rare but usually occurs in adolescents with an immature skeletal system. This paper reports a 15-year-old male who complained of knee pain after a bicycle accident. The initial radiographs and magnetic resonance imaging showed a bony bruise of the patella with signal change on the medial meniscus. After conservative treatment with immobilization for four weeks, he slipped down, and eccentric forced flexion of the knee was applied. This second injury caused a sleeve fracture of the superior pole of the patella. After splint immobilization for five weeks, the patient showed adequate function of the quadriceps and range of motion. Among the cases collected, some patients showed a similar history of sleeve fracture of the superior pole of the patella after serial knee injuries. KCI Citation Count: 0